Coagulation Factor and Hemostatic Protein Content of Canine Plasma after Storage of Whole Blood at Ambient Temperature. (27th January 2014) - Walton, J.E.; Hale, A.S.; Brooks, M.B.; Boag, A.K.; Barnett, W.; Dean, R.
<x xml:space="preserve">Abstract</x> Background Standard practice in canine blood banking is to produce fresh frozen plasma (FFP) by separating and freezing plasma produced from blood within 8 hours of collection. Within canine blood donation programs, this can limit the number of units collected. Hypothesis/Objectives The aim was to compare the coagulation factor and hemostatic protein content (CF&HPC) of plasma produced from blood stored at ambient temperature for 8, 12, and 24 hours. Another aim was to compare the CF&HPC between Greyhound types and other breeds. Animals None. Methods In vitro study. A convenience sample of 58 units of canine blood from a blood donor pool was processed to prepare and freeze plasma 8, 12, or 24 hours following collection. Results Regardless of time of processing, the units contained therapeutic CF&HPC. Frozen plasma prepared after 24 hours had significantly higher factor VIII (P = .014) and factor X (P = .03) when compared with the frozen plasma prepared at 8 hours. Factor X (P < .01), fibrinogen (P < .01), and vWF (P = .04) were significantly lower in plasma collected from Greyhound types than in plasma collected from other breeds. Conclusions and Clinical Importance Storing whole blood for up to 24 hours is a suitable method for producing FFP. Lower values for some coagulation factors and hemostatic proteins in plasma produced from Greyhound types would not preclude these dogs as FFP donors.